(untitled) (American Journal of Innovation in Science and Engineering, 2023)
Electric power systems play a significant role in modern society, serving billions of people. Therefore, there has been growing concern about the reliability and efficiency of the existing power systems; utilities are looking for technology to alleviate their concerns. One of the major concerns associated with voltage demand, is about system strength. System strength refers to the ability to withstand fault events, to maintain and control voltage waveform following these events. This paper aims to fill this gap by introducing synchronous elastic systems, using the SPN model, a connection strategy to improve frequency and voltage stability. In order to reach a more precise control effect, two working cases are considered for demonstrating the proposed control algorithm – droop control using SPN model. Droop control is realized by simulating the droop characteristics of generators and controlling the output voltage and frequency of the voltage source inverter (VSI) according to output power variation. Petri nets are classical tools for modelling and analyzing discrete event systems which are too complex to be described by automata or queuing models. The structural mechanism of the controller is based on the SPN model, which improves the problem of static error in the control of AC variables. The frequency domain characteristics are compared in detail and relevant parameters are designed. Controlling harmonic voltage levels within specified limits at the weakest point on the network ensures that other network locations will have better performance, hence, this study is highly appreciated.